Occupational choice, number of entrepreneurs and output: Theory and empirical evidence with Spanish data - Vicente Salas-Fumás; J. Javier Sanchez-Asin; David J. Storey (SERIEs - Journal of the Spanish Economic Association, 2014)
This paper extends the (Lucas, Bell J Econ 9:508-523,1978) model of occupational choices by individuals with different skills, beyond the simple options of self-employment or wage-employment, by including a second choice for the self-employed. That is, an option to hire employees and so become self-employed with employees (SEWEs), or to be self-employed without employees (SEWNEs). We solve for the market equilibrium and examine the sensitivity of relative sizes of occupational groups, and of the level of productivity, to changes in the exogenous parameters. The results show that the positive (negative) association between number of SEWEs (SEWNEs) and productivity, observed in the Spanish data, can be explained, under certain conditions, as the result of cross-region and time differences in average skills. These findings point to the importance of distinguishing between SEWEs and SEWNEs in drawing valid conclusions concerning any link between entrepreneurship and economic development.
Keywords: J24; L26; D24; 330; Occupational choice; Self-employment; Entrepreneurship; Entrepreneurial skills; Spanish economy